A 1, 1‐Carboboration Route to Bora‐Nazarov Systems. Issue 11 (17th August 2015) - Ge, Fang; Türkyilmaz, Fatma; Daniliuc, Constantin G.; Siedow, Melanie; Eckert, Hellmut; Kehr, Gerald; Erker, Gerhard
Abstract Hydroboration of the conjugated enynes 1 a and 1 b with Piers' borane [HB(C6F5)2] gave the respective dienylboranes trans‐2 c and trans‐2 d. Their photolysis resulted in the formation of the dihydroborole products 3 c and 3 d. Both were converted to their pyridine adducts 5 c and 5 d, respectively. Compounds 3 c and 5 c, d were characterized by X‐ray diffraction. The reaction of the bis(enynyl)boranes 6 a and 6 b with B(C6F5)3 resulted in the formation of the dihydroboroles 7 a and 7 b, respectively. This reaction is thought to proceed by 1, 1‐carboboration of one of the enynyl substituents at boron to generate the dienylborane intermediates 8 a/8 b, followed by thermally induced bora‐Nazarov ring‐closure and subsequent stabilizing 1, 2‐pentafluorophenyl group migration from boron to carbon. Compound 7 a was characterized by X‐ray diffraction and solid‐state 11B NMR spectroscopy.